2017
DOI: 10.1016/j.omtn.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA HCAL Facilitates the Growth and Metastasis of Hepatocellular Carcinoma by Acting as a ceRNA of LAPTM4B

Abstract: Long noncoding RNAs (lncRNAs) are a new class of regulatory noncoding RNAs. Emerging evidences indicate that lncRNAs play a critical role in the development of hepatocellular carcinoma (HCC). Although several lncRNAs have been annotated, the association of most lncRNAs with HCC is unknown. In this study, we investigated lncRNA alterations in HCC by performing lncRNA microarray analysis. We identified a novel lncRNA called HCC-associated lncRNA (HCAL) that was highly expressed in HCC tissues. HCAL upregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 35 publications
(39 reference statements)
0
58
0
Order By: Relevance
“…Similarly, lncRNA HOTAIR may function as a ceRNA to regulate HER2 expression through competition for miR‐331‐3p, thus playing an oncogenic role in gastric pathogenesis . Other studies also showed that ceRNAs were involved in the tumorigenesis of multiple cancer types, including prostate, breast, liver and lung cancers and so on . Although ceRNA research is still in its initial stages, exploration of ceRNA interplay in cancer will provide new insight into mechanisms underlying the pathogenesis of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, lncRNA HOTAIR may function as a ceRNA to regulate HER2 expression through competition for miR‐331‐3p, thus playing an oncogenic role in gastric pathogenesis . Other studies also showed that ceRNAs were involved in the tumorigenesis of multiple cancer types, including prostate, breast, liver and lung cancers and so on . Although ceRNA research is still in its initial stages, exploration of ceRNA interplay in cancer will provide new insight into mechanisms underlying the pathogenesis of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA in the cytoplasm could provide a multi-hued palette of regulatory capacities at posttranscriptional level, such as impact on the half-life or translation potential of mRNA (Batista and Chang, 2013). Recently, emerging studies pointed out that cytoplasmic lncRNA could function as 'miRNA sponges' to inhibit miRNA function with high efficiency and specificity Salmena et al, 2011;Song and Yin, 2016;Sun et al, 2017;Xie et al, 2017). To clarify whether LINC01436 could function as miRNA sponges, we started with microarray profiling and TCGA data to detect differentially expressed miRNA in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs exert their regulatory functions through various mechanisms, including lncRNA‐miRNA interaction, lncRNA‐mRNA interaction. lncRNA‐protein interaction, and epigenetic silencing . Recently, the lncRNA‐miRNA interaction has attracted a lot of interest.…”
Section: Introductionmentioning
confidence: 99%